The epidemiological profile of knee injury pattern among different divisional football players - Atiqur Rahman Khan; Mohammad Jobair Khan; Mohammad Delwer Hossain Hawlader (Turkish Journal of Kinesiology, 2019)
The complete scenario of number and factors of knee injuries among the male footballers is intangible; therefore, it would seem essential to compute the injuries in relation to field condition and to show the nature and type of injuries including the possible risk factors. In a total of 200 of 215 soccer athletes playing at least one year professionally were randomized with the age range 14 - 40 years recruited from different divisional clubs. All information collected through questionnaires from five football clubs who were participating in the tournament from March 2011 to February 2012.   In total, from 200 players, 116 of them suffered soft tissue injuries (29 per 100 players) in the knee on average 27 years of age. A higher percentage of injury explored in midfielder 35.5%, and the ligament was the most common 63.8% soft tissue injury. 59% participant noted about lack of a particular exercise regimen for the knee. Poor ground condition significantly associated with the injury (x2= 6.7503, p= 0.034). There was a significant association (OR= 2.745, x2= 11.1048, p= 0.0010) between performing particular exercise (41%) and non-performing (59%); and knee injuries. Most injuries were characteristically mild (58.6%). Majority of injuries occurred in contact (74.1%), during games (44%). The significant relationship found between warm up and knee injury (OR= 2.110, x2= 5.8808, p= 0.0107). Physiotherapy treatment 39.6% was the second choice of management. Our findings revealed that midfielders suffered a greater percentage of knee injuries compared to other positions, with injuries being more predominant during match play.